The Future of China's Past Reflections on the Meaning of China's Rise. - Welter, Albert (State University of New York Press, 2023)
Addresses the question of China's rise and what it portends for the future.
Description based upon print version of record.
Keywords: China -- Civilization -- 21st century.; Chine -- Civilisation -- 21e siècle.; HISTORY / Asia / China.; Civilization; Forecasting; China